TECHNOLOGICAL AND BREAD BAKING TRAITS OF TRITICALE - E. N. Shabolkina; N. V. Anisimkina; M. V. Belyaeva (Зерновое хозяйство России)
Winter triticale, carrying the genes of its parental forms, has taken both the positive properties of wheat and rye (a significant amount of protein, presence of gluten, content of biologically active aromatic substances) and negative (a large amount of soluble albumin and globulin proteins and especially high activity of amylolytic enzymes). The weather conditions during the vegetation, as well as the varietal characteristics of this grain crop are of great influence on the grain quality. Therefore, cultivation of winter triticale with high biochemical and baking properties is an important problem in the conditions of the Steppe Zavolzhie, in the zone of risky farming. The article presents the results of study conducted during 2007–2016 on the experimental plots of the Samarsky RIA. To establish an objective assessment of winter triticale quality, there was carried out a study of biochemical, technological and baking traits. Under favorable conditions for plant growth and development, winter triticale accumulates a significant percentage (18.3–18.8) of protein in kernels; forms grain with strong starch and low enzymatic activity (252–274 c of “falling number”, 300–520 a. u. of water-flour viscosity). Analysis of the baking traits of triticale has showed that it is necessary to take into account all the subtleties related to the dough process and the recipe. Due to the low gas-holding capacity and dough thinning (dilution), triticale is almost never used in its pure baking form. When 50 and 70% of triticale is added to flour, there is a significant improvement in bread quality, namely in volume and in texture, in dimensional stability and sensory characteristics (6.2 cm3/g of specific volume; 4.5 points of baking). The study results show that more attention should be paid to the varietal characteristics of winter triticale in the conditions of the Steppe Zavolzhie.